Subglacial discharge effects on basal melting of a rotating, idealized ice shelf - I. Vaňková; X. Asay-Davis; C. Branecky Begeman; D. Comeau; A. Hager; M. Hoffman; S. F. Price; J. Wolfe (The Cryosphere)
When subglacial meltwater is discharged into the ocean at the grounding line, it acts as a source of buoyancy, enhancing flow speeds along the ice base that result in higher basal melt rates. The effects of subglacial discharge have been well studied in the context of a Greenland-like, vertical calving front, where Earth's rotation can be neglected. Here we study these effects in the context of Antarctic ice shelves, where rotation is important. We use a numerical model to simulate ocean circulation and basal melting beneath an idealized three-dimensional ice shelf and vary the rate and distribution of subglacial discharge. For channelized discharge, we find that in the rotating case, total melt-flux anomaly increases with two-thirds power of the discharge, in contrast to existing non-rotating results for which the melt-flux anomaly increases with one-third power of the discharge. The higher melt-flux anomaly with discharge is attributed to a more extensive area of the ice-shelf base being exposed to direct high melting by the rising plume as it is deflected due to Earth's rotation and its path is prolonged. For distributed discharge, we find that in both the rotating and the non-rotating cases, the melt-flux anomaly increases with two-thirds power of the discharge. Furthermore, in the rotating case, the addition of channelized, subglacial discharge can produce either a higher or a lower ice-shelf basal melt-flux anomaly than the equivalent amount of distributed discharge, depending on its location along the grounding line relative to the directionality of the Coriolis force. This contrasts with previous results from non-rotating, vertical ice-cliff simulations, where distributed discharge was always found to be more efficient than channelized discharge at enhancing the terminus-averaged melt rate. The implication, based on our idealized simulations, is that melt-rate parameterizations attempting to include subglacial discharge effects that are not geometry- and rotation-aware may produce total melt-flux anomalies that are off by a factor of 2 or more.